(untitled) (Konturen, 2026)
Kafka’s short prose pieces often challenge our ability to decipher them, sometimes, seemingly, in inverse proportion to their brevity. This essay takes "The Trees" [Die Bäume] as an exploratory guide towards meeting that challenge, entertaining different reading methods that emerge through classroom discussion, methods that the text seems to both demand and disavow: ones that turn toward Kafka’s unsettled Jewish-Hebraic and European heritage, ones that invite students’ own experience, and ones that probe the nature of language itself. As a template of the reading process, and of teaching that process in turn, Kafka’s text points to a shared interpretive practice that may connect us to others while simultaneously enabling us to question who "we" really are.